KEMAMPUAN PEMECAHAN MASALAH SISWA SMP DALAM MENYELESAIKAN SOAL SPLDV DITINJAU DARI TIPE KEPRIBADIAN MBTI - Yesiana, Maria; Indrawatiningsih, Nonik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem-solving ability of junior high school students in solving Two-Variable Linear Equation System (SPLDV) problems is still relatively low, and this is influenced not only by mastery of mathematical concepts, but also by personality type, which shapes how students understand problems, plan strategies, and evaluate results, so the judging and perceiving dimensions of the MBTI are important to study because they relate directly to how students organize and complete mathematical tasks. This study aims to describe the problem-solving ability of eighth-grade junior high school students with judging and perceiving personality types in solving SPLDV problems. This study used a descriptive qualitative approach with a multiple case study design, involving two subjects (one judging type coded AR, one perceiving type coded WSL) selected through purposive sampling based on an MBTI questionnaire and a mathematics ability test at the moderate category, with data collected through the MBTI questionnaire, a mathematics ability test, an SPLDV test, and interviews, then analyzed based on Polya's four problem-solving stages. The results showed that both subjects were able to solve the SPLDV problem at all four stages; the judging-type subject worked sequentially and consistently on a single plan and then checked the results thoroughly in line with a structured characteristic, while the perceiving-type subject worked more flexibly, briefly considered an alternative approach, and checked the results more briefly in line with an adaptive characteristic. Thus, personality type did not affect the students' success in solving the problem, but did affect how they carried out the solving process.